“We Are What We Hear”: Metaphors in Contemporary Spanish and English Commercial Hits - Mariló CAMACHO DÍAZ,Dra. Mª Carmen FONSECA MORA (Fonseca, Journal of Communication, 2023)
The subliminal messages transmitted by means of metaphors in songs could influence the development of critical thinking among our youngsters which will reflect on their personality later in life. The aim of this article is to analyse the discourse of the most popular commercial songs in English and Spanish of song-writers and the values they convey to metaphorical compositions.